4(3n-1)=2n+2(5n-2)

Simple and best practice solution for 4(3n-1)=2n+2(5n-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3n-1)=2n+2(5n-2) equation:


Simplifying
4(3n + -1) = 2n + 2(5n + -2)

Reorder the terms:
4(-1 + 3n) = 2n + 2(5n + -2)
(-1 * 4 + 3n * 4) = 2n + 2(5n + -2)
(-4 + 12n) = 2n + 2(5n + -2)

Reorder the terms:
-4 + 12n = 2n + 2(-2 + 5n)
-4 + 12n = 2n + (-2 * 2 + 5n * 2)
-4 + 12n = 2n + (-4 + 10n)

Reorder the terms:
-4 + 12n = -4 + 2n + 10n

Combine like terms: 2n + 10n = 12n
-4 + 12n = -4 + 12n

Add '4' to each side of the equation.
-4 + 4 + 12n = -4 + 4 + 12n

Combine like terms: -4 + 4 = 0
0 + 12n = -4 + 4 + 12n
12n = -4 + 4 + 12n

Combine like terms: -4 + 4 = 0
12n = 0 + 12n
12n = 12n

Add '-12n' to each side of the equation.
12n + -12n = 12n + -12n

Combine like terms: 12n + -12n = 0
0 = 12n + -12n

Combine like terms: 12n + -12n = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 8x-10=2x+4 | | 2y-2=.14 | | y=(.5x-3) | | 5(b+9)+7= | | -7=-3c | | x/41+89=93 | | 10x+4x+2+9=4x+3+9x | | b^2+7b+2=-10 | | 0.2x+5=2 | | (2y+7)(3y-7)=0 | | x+3x+6x-8=180 | | 5/6x1/2 | | a-x+c=d | | 9x/5-3/2=6 | | 1500+.05x=1865 | | 56=14+7x | | 9n^3/3t^7r^3 | | (29b-3)-7(4b+3)=-4 | | 4x=2y-yx | | -(3x-6y-9)= | | 2/3k-9=5 | | -4=1x-12 | | 6u^2-22uv+20v^2=0 | | 5p-(-10)=-5 | | 23y/30-4=96y/5 | | 16x^2+18x=19 | | 37-63= | | 0=2.15+9.6x+(.5)(-9.81)(x^2) | | k+9=7.5 | | 5x-3(y-2)=2x+21 | | x+.14x=1234.62 | | 28=-2(3x-5) |

Equations solver categories